CHIGGERS (ACARINA, TROMBICULIDAE) OF MAXOMYS BARTELSII FOUND IN WEST JAVA, INDONESIA, WITH DESCRIPTIONS OF TWO NEW SPECIES - TUTI R HADI (Treubia, 1991)
A collection of chiggers infesting Maxomys bartelsii,a rat commonly found in the highlands of West and Central Java, was obtained during the extensive study of this particular rat species in 1970 - 1972 conducted by U.S. Naval Medical Research Unit No. 2 Jakarta Detachment. Two of the seven chigger species identified are considered as new species and described in this paper. Diagnostic characters and the Indonesian records of the other 5 species were included.